Rehtorien toimijuus johtamisen tavoitteissa ja käytännöissä - Lahti Inkeri; Mikkilä-Erdmann Mirjamaija; Iiskala Tuike (Hallinnon tutkimuksen seura, 2025)
Principals' agency in leadership goals and practice
This interview study examines the leadership goals and practices embodied in principals' professional agency. The framework of the study consists of agency and broad-based pedagogical leadership. The analysis used data- and theory-based content analysis. Based on the data three leadership styles embodying agency were created: survival, construction and development leadership style. The study shows that in all leadership styles, agency does not manifest itself as broad-based pedagogical leadership. This is due to the concentration of the leadership style in the day-to-day management of maintaining school activities. However, the realization of broad-based pedagogical leadership requires management of the symbolic and cultural sphere as well. Examining agency as a part of broad-based pedagogical leadership shows that leadership must be constantly developed.